Synergistic Insecticidal Effect of Photorhabdus luminescens and Bacillus thuringiensis against Fall Armyworm (Spodoptera frugiperda) - Chang, Ting-Yu; Hsieh, Chienyan; Wu, Li-Hsin (Agriculture (Basel), 2024)
Combining microbial products with different mechanisms of action can produce synergistic insecticidal effects and slow down the development of resistance. This study evaluated the insecticidal activity of mixtures containing the commercial Photorhabdus luminescens (Pl) strain ATCC 29,999, the local isolate Pl 2103-UV, and the commercial Bacillus thuringiensis subsp. kurstaki (Bt) ABTS-351 against Spodoptera frugiperda. As the proportion of Bt increased in the mixtures, insecticidal activity increased, with the synergistic ratios reaching 1.98 for ATCC 29,999 and 5.29 for 2103-UV at a1:5 Pl:Bt ratio, representing approximately twofold and fivefold reductions, respectively, in the Bt dosage required for mortality. Hemolymph analysis revealed the highest Pl bacterial loads in the 1:5 treatments within the S. frugiperda hemocoel. Histopathology also showed exacerbated midgut vacuolation in the 1:5 ATCC 29,999:Bt treatment. Whole-genome analysis showed that 2103-UV produced more porins, potentially contributing to its higher insecticidal activity. This study demonstrated that Bt assists the invasion of Pl into the hemocoel and enhances synergistic insecticidal efficiency. The findings provide a reference for integrating Pl with other microbial products to sustainably manage significant and severe lepidopteran pests.